Re‐evaluation of birth trends and pregnancy complications among female urologists: Have we made any progress?. Issue 5 (25th May 2020) - Scott, Victoria C. S.; Lerner, Lori B.; Eilber, Karyn S.; Anger, Jennifer T.; Ackerman, A. Lenore
Abstract: Aims: Females are becoming surgeons at ever‐increasing rates and doing so while many have or wish to have children. This study follows up on a 2007 effort to study the problems and conditions such women faced. We ask here if these challenges are different after a decade that included changes in working rules. Methods: A survey was sent to all female American Board of Urology diplomates. Birth trends, pregnancy complications, infertility service requirements, and satisfaction were evaluated in respondents (n = 183) and compared to the previous survey of female urologists who completed residency before August 2007 as well as Center for Disease Control data. Results: Seventy‐six physicians completed the survey who were residents before 2007, while 107 replied who experienced residency after. The first group's average age was 50.2 and the second's 38.3. Overall, these women gave birth 6 to 7 years later than the US mean. Complications did not decrease, infertility occurred at similar levels, and both were higher than US norms. Length of maternity leave correlated with respondents' level of overall satisfaction. The most positive responses came from those with more than 8 weeks off ( P  = .002). Conclusions: Women practicing in urology gave birth later, had greater fertility issues, used assisted reproductive technology (ART) more and reported a higher level of at least one complication during pregnancy than American women overall. Changes in hours and awareness of this issue have not made giving birth a healthier event for these physicians. Further investigation into factors other than work hours is needed.